Penggunaan Agregat Sungai Batu Mallopie Kabupaten Barru Sebagai Bahan Campur Beton - Alri Paembonan; Erni Rante Bungin; Desi Sandy (Paulus Civil Engineering Journal, 2025)
Concrete is a component that is applied to construction other than wood and steel because of its advantages, resistant to fire, corrosion, durable and easy to form one of the elements of concrete formation in the form of aggregate that is easy to get, one of which is aggregate from the Batu Malopie River, Barru Regency, coarse aggregate is the main maretial element in concrete that can affect the quality of the concrete so that this study varies the size of the coarse aggregate used, namely 1" and 3/4". The purpose of this study is to find out the character values of fresh concrete, namely the slump value and fill weight as well as the results of compressive strength, pull, bending strength, along with elastic modulus. The method used for this test is experimental in a laboratory that refers to SNI 7656-2012. The results of the fresh concrete test were obtained that the slump test values for both variations still met  the planned slump,  which was between 2.5-10 mm, and the results of the concrete content weight test met the concrete weight requirements of 2300-2400 kg/m3, the results obtained in the hard concrete test for compressive strength, tensile strength, bending strength and modulus of elasticity, through the planned quality of 25 Mpa with variations of 1" and 3/4" in the 28-day test met the planned quality.  For the 3/4" coarse aggregate variation, the quality result was obtained larger than the 1" variation.